2020
DOI: 10.3892/etm.2020.8499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol on LC3II and mTOR/p‑mTOR expression during ischemia‑reperfusion myocardium injury in rats with type 2 diabetes mellitus

Abstract: To investigate the effects of propofol on myocardial ischemia reperfusion in rats with type 2 diabetes, male adult rats were divided into five groups: Sham-operation (CC), ischemia-reperfusion (CI), low-dose propofol (LP), moderate-dose propofol (MP) and high-dose propofol (HP). The LP, MP and HP groups were administered with 6, 12 and 24 mg/kg/h propofol, respectively, prior to occlusion. Heart rate (HR), left ventricular systolic pressure (LVSP) and the rate (dp/dt max) of left ventricular pressure rise in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…50 Even after controlling for demographic variables, the improvement in quality of life was significantly related to the number of years and frequency of practicing Tai chi. [51][52][53] In previous studies, diabetic patients who exercised Tai chi for more than 12 weeks reported higher cutaneous vascular conductivity and better peripheral nerve conduction velocity of bilateral median and tibial nerves. [54][55][56] These findings suggest that Tai chi exercise can improve sensory function and neuropathy related symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Even after controlling for demographic variables, the improvement in quality of life was significantly related to the number of years and frequency of practicing Tai chi. [51][52][53] In previous studies, diabetic patients who exercised Tai chi for more than 12 weeks reported higher cutaneous vascular conductivity and better peripheral nerve conduction velocity of bilateral median and tibial nerves. [54][55][56] These findings suggest that Tai chi exercise can improve sensory function and neuropathy related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…50 Even after controlling for demographic variables, the improvement in quality of life was significantly related to the number of years and frequency of practicing Tai chi. 51-53…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine attenuates cell damage and apoptosis in H9c2 cardiomyocytes [ 56 ] and inhibits pyroptosis in myocardial ischemia–reperfusion injury in rats [ 57 ]. Propofol also reduced cardiac injury via inhibition of intrinsic apoptotic pathways [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it may prevent cerebral ischemia-triggered autophagy activation and cell death through the NF-κB/p53 signaling pathway ( Cui et al., 2013 ). A recent report shows that propofol significantly reduces serum levels of LC3-II and mTOR, which is associated with inhibition of autophagy in myocardial cells from rats with type 2 diabetes mellitus ( Wang et al., 2020b ). Berberine and melatonin are potential drugs to prevent excessive autophagy in cardiomyocytes via suppressing upstream AMPK signaling, which leads to amelioration of cardiac ischemia/reperfusion injury ( Huang et al., 2015 ; Chen et al., 2018c ).…”
Section: Use Of Autophagy Modulators In the Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%